ANALISIS PROGRAM PEMBERDAYAAN EKONOMI UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA - Singgih Purnomo; Rahmawati Setyani (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
This research is to analyze the economic empowerment program to improve the welfare of village communities in Giriwoyo District, Wonogiri Regency. The research method used is a qualitative method with a phenomenological approach with data collection techniques in the form of observation, interviews and documentation. The research results show that KKNT activities in Giriwoyo District Wonogiri Regency have been carried out well, even though they are faced with various problems in the field. Based on research results, KKNT activities in Giriwoyo District Wonogiri Regency have provided benefits for students and had a positive impact on village communities. KKNT activities are effective as a model that is able to integrate the roles of universities, government and village communities in economic empowerment efforts to improve the welfare of village communities in Giriwoyo District Wonogiri Regency. The result of the research show that economic empowerment programs that can help improve the welfare of village communities in Giriwoyo District, Wonogiri Regency include increasing public health awareness, increasing community literacy, increasing understanding of implementing healthy clean living behavior, digitalizing micro, small and medium enterprises in the Giriwoyo District area, Wonogiri Regency and increasing local agricultural potential. The results of community economic empowerment are shown by increasing community welfare through programs to increase public health awareness, program to increase community literacy and programs to increase understanding of clean and healthy living behavior. Apart from that, the results of community economic empowerment are shown by increasing community income through the digitalization program for micro, small and medium enterprises and optimizing local agricultural potential.